The evaluation of mLearning implementation model for English Language learning via Fuzzy Delphi method - Abdullah, M.R.T.L. (Universiti Putra Malaysia, 2018)
This paper introduces Fuzzy Delphi method as an educational tool to evaluate a technology-mediated education implementation model as part of a larger study. Specifically, the aim of the present study is to evaluate a mLearning implementation model as learning support for undergraduate students in formal language learning which was developed by the authors prior to this study. The study adopted the Fuzzy Delphi method to evaluate the model. Overall, from the findings presented in this paper, as the defuzzification values for all items in the questionnaire exceeded the minimum value of 33.6, the findings conclusively suggest that the participants have consensually agreed to all four aspects of evaluation of the model: 1) suitability of the elements (learning activities), 2) domain classification of the learning activities, 3) relationships among the learning activities, and 4) suitability of the model in teaching and learning activities in assisting students to fulfill their language learning needs and course outcomes. Thus, according to the participants or experts of the study, based on these aspects, the model is suitable to serve as a guide in the implementation of mLearning as learning support for undergraduate formal English language learning for Professional and Communication Skills course. The findings not only serve to introduce mLearning implementation model for language learning but also contribute to how the Fuzzy Delphi method could innovate assessment and evaluation of technology aided learning initiatives like mLearning. Â© Universiti Putra Malaysia Press.